Analisis Pengaruh Sistem Pembelajaran Blok terhadap Beban Belajar Mahasiswa Fakultas Teknik Universitas Negeri Medan (UNIMED) - Subaedah, Sitti; Gebrila, Gebrila; Ritonga, Putri Hidayanti; Rusda, Sabila; Tarigan, Sucy Novika (VISA: Journal of Vision and Ideas, 2025)
This study aims to analyze the effect of the block learning system on the learning load of students at the Faculty of Engineering, State University of Medan (UNIMED). The block learning system is applied to group learning materials in a certain period of time, which aims to improve concentration and learning efficiency. The research method used is interviews, where data is collected through direct interaction with students involved in the block learning system. The results of the study indicate that the implementation of the block learning system has a significant impact on students' learning load, both in terms of time management, concentration, and the level of difficulty of the material being studied. However, some students also feel that this system provides greater pressure related to the time to complete assignments and exams. This study is expected to provide useful recommendations for the development of a more effective learning system in the future.